2002
DOI: 10.1063/1.1498007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast optical switching properties of single-wall carbon nanotube polymer composites at 1.55 μm

Abstract: Using a pump-probe method with a 150 fs laser at the wavelength of 1.55 m, we have experimentally demonstrated that single-walled carbon nanotubes ͑SWNT͒ have an exciton decay time of less than 1 ps and a high third-order polarizability, which is reasonably interpreted as due to their azimuthal symmetry. These experimental results reveal that a SWNT polymer composite may be a candidate material for high-quality subpicosecond all-optical switches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
159
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(164 citation statements)
references
References 19 publications
5
159
0
Order By: Relevance
“…They found that MWNT/PmPV composite showed a strong nonlinear signal, which is very applicable in the area of high performance nonlinear optical devices. Chen et al [117] reported that SWNT/polymer composites, especially SWNT/PI composite, not only had an optical decay time of less than 1 ps, but also a high third-order nonlinear polarizability, which makes the composite a promising material for high-quality subpicosecond all-optical switches. A few papers have studied the electromagnetic and microwave absorption properties of polymer composites reinforced with CNTs.…”
Section: Other Functional Properties and Application Of Cnt/polymer Cmentioning
confidence: 99%
“…They found that MWNT/PmPV composite showed a strong nonlinear signal, which is very applicable in the area of high performance nonlinear optical devices. Chen et al [117] reported that SWNT/polymer composites, especially SWNT/PI composite, not only had an optical decay time of less than 1 ps, but also a high third-order nonlinear polarizability, which makes the composite a promising material for high-quality subpicosecond all-optical switches. A few papers have studied the electromagnetic and microwave absorption properties of polymer composites reinforced with CNTs.…”
Section: Other Functional Properties and Application Of Cnt/polymer Cmentioning
confidence: 99%
“…2 The use of nanotube suspensions results in poorly resolved data, because a large background signal inevitably exists and an inhomogeneously deposited film and dispersed composite make the absorption and reflection measurements in the same sample difficult. These drawbacks could lead to a misunderstanding of the intrinsic optical properties of SWNTs.…”
mentioning
confidence: 99%
“…Very recently, intensive studies on the nonlinear optical properties of SWNTs have been carried out theoretically 1 and experimentally. [2][3][4] It is believed that SWNTs can be used in the fabrication of optical limiting and switching devices due to their nonlinear optical properties upon absorption [4][5][6] and its fast decay time of less than 1 picoseconds. 2,[7][8][9] These nonlinear properties are related to the third-order nonlinear susceptibility χ (3) , which is considered to be a complex quantity: 10 ( ) ( ) ( 3…”
mentioning
confidence: 99%
“…Recent reports announcing ultrafast saturable absorption in single-walled carbon nanotubes (SWCNTs) motivated development of a ultrafast passive mode-locker based on SWCNTs [5,6]. After the first demonstration of SWCNT-SA mode-locking in a fiber laser that can tolerate large insertion losses [7], SWCNT-SAs also have been successfully applied to passively mode-locked bulk solid-state lasers, such as Yb compared to former passive devices including SESAMs.…”
Section: Introductionmentioning
confidence: 99%